2021
DOI: 10.1136/jitc-2021-002794
|View full text |Cite
|
Sign up to set email alerts
|

Society for Immunotherapy of Cancer (SITC) clinical practice guideline on immunotherapy for the treatment of hepatocellular carcinoma

Abstract: Patients with advanced hepatocellular carcinoma (HCC) have historically had few options and faced extremely poor prognoses if their disease progressed after standard-of-care tyrosine kinase inhibitors (TKIs). Recently, the standard of care for HCC has been transformed as a combination of the immune checkpoint inhibitor (ICI) atezolizumab plus the anti-vascular endothelial growth factor (VEGF) antibody bevacizumab was shown to offer improved overall survival in the first-line setting. Immunotherapy has demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 231 publications
1
30
0
Order By: Relevance
“…In summary, for Child A cirrhosis patients with satisfactory performance status, atezolizumab–bevacizumab is now recommended as the first-line therapy. This is consistent with the ASCO 2020 guideline [ 14 ], the Society for Immunotherapy of Cancer 2021 guideline [ 26 ], and the recommendation from the EASL [ 27 ].…”
Section: Systemic Therapies For Advanced Hccsupporting
confidence: 86%
“…In summary, for Child A cirrhosis patients with satisfactory performance status, atezolizumab–bevacizumab is now recommended as the first-line therapy. This is consistent with the ASCO 2020 guideline [ 14 ], the Society for Immunotherapy of Cancer 2021 guideline [ 26 ], and the recommendation from the EASL [ 27 ].…”
Section: Systemic Therapies For Advanced Hccsupporting
confidence: 86%
“…Furthermore, in a recently published update analysis with a median follow-up of 15.6 months, Atezo/Bev therapy showed a 5.8 month longer median OS than sorafenib [ 6 ] and a safety profile consistent with the primary analysis [ 5 ]. Objective response occurred in 30% of patients treated with Atezo/Bev therapy, and 74% of patients obtained disease control, so this therapy now serves as a potent front-line chemotherapy [ 7 ]. On the other hand, 19% of treated patients were reported to be non-responders [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Despite the superior design concept of D-TACE, a previous study demonstrated that D-TACE enhanced tumor response but did not improve survival in patients with BCLC stage A and B. 24 Since the mode of drug-delivery between D-TACE and C-TACE is different, there is need to explore the difference in efficacy between a combination of D-TACE and ICIs, (the drugs recommended for advanced HCC 25 ), and a combination of C-TACE and ICIs.…”
Section: Discussionmentioning
confidence: 99%